Video marketing like a pro : a practical guide to creating and publishing videos that convert. - Willaerts, Clo, ....- (Leuven : LannooCampus, 2021)
For years, trend reports have highlighted the popularity of web videos. And each time, they noted that increasing numbers of people were enjoying videos on YouTube or RikRok, or participating in livestream events on Facebook and Twitch. Self-producing those videos became more and more popular and some mandaged to make a lot of Money.
Keywords: Marketing; Video